2017
DOI: 10.18203/2349-3291.ijcp20170363
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco and betel nut use among school going adolescents of government high school of Himmatnagar city, Gujarat, India: a cross sectional study

Abstract: Background: Adolescence period is very crucial in the life of an individual, when major physical, psychological and behavioral changes take place. Tobacco and areca nut use among school going adolescent is becoming a major public health problem. The aim was to determine the prevalence and pattern of smokeless tobacco and betel nut use among school going adolescents.Methods: The study was a cross sectional study. After taking the permission of principal of Government high school and consent of the parents of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…In study done by Prajapati N et al, tobacco use among male adolescents were also significantly high than among female adolescents. 1 In Majara J P et al, prevalence of tobacco use among males was found to be significantly high (42.1%) than among females (17.0% ) in the age group of 13-15 years. 11 Out of 230 male adolescents who had addiction, majority of adolescents (57.3%) consume tobacco in the form of gutkha and 56.1% male adolescents had addiction since 4 to 9 years.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…In study done by Prajapati N et al, tobacco use among male adolescents were also significantly high than among female adolescents. 1 In Majara J P et al, prevalence of tobacco use among males was found to be significantly high (42.1%) than among females (17.0% ) in the age group of 13-15 years. 11 Out of 230 male adolescents who had addiction, majority of adolescents (57.3%) consume tobacco in the form of gutkha and 56.1% male adolescents had addiction since 4 to 9 years.…”
Section: Resultsmentioning
confidence: 94%
“…In study done by Prajapati N et al, majority of adolescents (63.4%) consume tobacco in the form of gutkha and 76.3% male adolescent had addiction since 1 to 3 years. 1 Among the tobacco users, the mean age at the start of any tobacco use was 11.3 years with an SD of 2.52 years. Out of 73 female adolescents who had addiction majority of adolescents (89%) consume betel nut and 64.3% female adolescents had addiction since 1 to 3 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experience and behavior during these formative years can influence lifelong health, as well as put current health at risk. [11]…”
Section: Discussionmentioning
confidence: 99%